KARAKTERISTIK WISATAWAN MANCANEGARA DI INDUSTRI PERHOTELAN - muhammad rival; Yen Polisda (Jurnal Pariwisata Bunda, 2023)
Indonesia is one of the countries that is a favorite destination for foreign tourists. This affects the hotel industry as one of the tourism sectors. At a hotel, a front desk agent is one of the parts in the front office department that deals directly with either domestic tourists or with foreign guests. Servicing  foreign guests, front desk agents meet and serve foreign guests from various countries who have different characteristics. This research was conducted to see how employees perceive the characteristics of foreign guests who check-in at I Hotel Baloi, Batam.This descriptive research used interviews as data collection technique. 4 (four) front desk agents and one student trainee (assigning as a front desk agent)  were selected as informants from I Hotel Baloi. The results showed that every foreign guest who came had different characters according to their country of origin. The characteristics of foreign guests who come also affect the performance and work environment of front desk agents. .